Modern interpretations of traditional Evenki beadwork ... - Campbell, Sandy (University of Alberta Library, 2014)
Young women model modern beaded clothing creations by Benchik Natalya Vladimirovna, granddaughter of traditional beadworker Semenova Polina Ivanova. ...